Optogenetics, A Futuristic Panacea in Genetics - Dito Anurogo; Taruna Ikrar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractOptogenetics is the constellation of optics, genetics and bioengineering which unites genetic engineering with optics to notice and manage the function of genetically targeted groups of cells with light, often in the intact animal, via light-sensitive microbial membrane proteins (opsins). Light-sensitive genes specifically including the genetically targeted light-gated channels channelrhodopsin-2 (ChR2) and halorhodopsin (NpHR) result in intracellular ion flow during optical illumination. Afterward, the neurons encounter a series of changes resulting from membrane depolarization or hyperpolarization. Although the rooted origins of optogenetics is from neuroscience, it can be potentially applied in neuropsychocardioncology (neurology, psychiatry, oncology, and cardiology).This critical review will explicate a comprehensive summary of the roles of optogenetics in the field of neuropsychocardioncology.Optogenetics can be potentially developed as neuroprosthetics and direct NpHR in the management of spastic movement disorders. Optogenetics can control of larynx muscle contraction in vivo, using both transgenic ChR2 expressing mice and viral transduction of muscle.In epilepsy, the efficacy of optogenetics is proved. Pyramidal cells in the cortex were transduced with halorhodopsin, and photoinhibition of the neurons decreased electrical seizure activity. Optogenetic and DREADD technologies are in their early stages, particularly with respect to PD research or therapy.In autism and schizophrenia, behavioral deficits may arise from elevation in the cellular balance of excitation/inhibition (E/I balance) within neuronal microcircuits. This hypothesis was tested by optogenetically elevating the E/I balance in the medial-prefrontal cortex using a step-function opsin (SSFO), together with red-shifted opsins (C1V1). Increased excitation in excitatory pyramidal neurons, lead to social-cognitive dysfunctioning which are similar to those seen in autism. Cortical gamma oscillations are an indicator of enhanced information processing, which is highly affected in schizophrenic patients.Using optogenetic technology, researchers divulge the characterization of phosphatidylinositol 3-kinase (PI3K) in Rac1-dependent lamellipodial motility in PC-3 prostate cancer cells. PI3K, acting downstream of Rac1, has an important role in the initiation of lamellipodial extension, which underlies prostate cancer cell invasion and metastasis. As in Parkinson, human cells can be engineered to deliver the excitatory (hM3Dq receptor) and/or the inhibitory (hM4Di receptor) form so that cellular activity may be turned up or down.The optogenetic TCU (tandem-cell-unit) strategy can be valuable in appraising tissue graft integration and cell delivery in the myocardium during cardiac tissue repair procedures. Low-energy pacing strategies can be srutinized by optogenetic investigations. Specifically, optical stimulation can be aimed for strategic structures of the conduction system. Optogenetic studies have already contributed to a better understanding of the neural circuits affected in many disorders. A conceptual and mutual understanding of multidisciplinary approaches and collaboration will enable researchers, clinicians, stakeholders, government develop and apply optogenetics in comprehensive medical services and health care.Keywords: optogenetics, opsins, neuropsychocardioncology, SSFO, DREADD, TCU.